Model‐Free Estimation of Energy‐Transfer Timescales in a Closely Emitting CdSe/ZnS Quantum Dot and Rhodamine 6G FRET Couple. Issue 21 (23rd October 2018) - Bharadwaj, Kiran; Koley, Somnath; Jana, Subhra; Ghosh, Subhadip
Abstract: Analysis of Förster resonance energy transfer (FRET) in nanoparticles is often complicated by a number of factors, such as close emission band positions of the donor and acceptor, the presence of simultaneous photoinduced electron transfer, fluorescence blinking, and natural excited‐state decay processes. To address these concerns, mostly from materials chemists and biologists, herein, a state‐of‐the‐art FRET analysis method that utilizes the bright green emission of a CdSe/ZnS core/shell quantum dot (QD) is proposed. The uniqueness of this model‐free FRET analysis demonstrates the potential of these QDs to be part of an efficient FRET assay in molecular ruler applications. Molecular distance calculations relying on the proposed FRET analysis complement nicely with the expected donor‐to‐acceptor separation distances; the QD, as a photoluminescent marker, is electrostatically attached to a compatible fluorescent dye, rhodamine 6G. The beneficial aspects of the model‐free FRET analysis provide many possibilities, including the use of low cytotoxicity QD‐based FRET assays as a next‐generation molecular ruler for the accurate estimation of distances inside a biological system. Abstract : Model‐free analysis of FRET : A state‐of‐the‐art FRET analysis method utilizing the bright green emission of CdSe/ZnS core/shell quantum dot (QD) is proposed (see figure). The beneficial aspects of this model‐free FRET analysis provide many possibilities, including the utilization of QD‐based FRET assays as a next‐generation molecular ruler for the accurate estimation of distances inside a biological system.